Some approximation results for generalized Kantorovich-type operators - Mursaleen, Mohammad; Khan, Faisal; Khan, Asif; Kilicman, Adem (Springer Open, 2013)
In this paper, we construct a new family of operators, prove some approximation results in A-statistical sense and establish some direct theorems for Kantorovich-type integral operators.